Morphological and molecular profiling of Spirogyra from northeastern and northern Thailand using inter simple sequence repeat (ISSR) markers - Wongsawad,P. (King Saud University, 2015)
© 2014 The Authors. Green algae, Spirogyra (Chlorophyta), are found in a wide range of habitats including small stagnant water bodies, rivers, and streams. Species identification of Spirogyra based on morphological characteristics has proven to be a difficult process. An accurate identification method is required to evaluate genetic variations. This study is aimed at investigating the molecular profiling of 19 samples of Spirogyra from northern and northeastern Thailand. The morphological characteristics of each sample were recorded, viz. cell dimensions (width and length), along with the number and arrangement of chloroplast spirals/pyrenoids. With regard to a correlation of the biological and ecological parameters, conductivity was clearly significantly related to the number of pyrenoids. While DO is negatively related to the number of chloroplast spirals. Molecular studies with 10 ISSR primers were amplified to examine the DNA fingerprints. Morphological characters were determined to be significantly different by revealing 5 traits (P <. 0.05) for all specimens. In addition, the DNA markers of all specimens were investigated using 10 ISSR primers. The results show that the PCR technique amplified 108 fragments. An analysis of the DNA fragments grouped all samples by ISRR-PCR, which were then separated into two groups according to their distribution.